REDD+ as 'inclusive' neoliberal conservation: the case of Lindi, Tanzania. Issue 3 (3rd July 2017) - Scheba, Andreas; Scheba, Suraya
ABSTRACT: In recent years, market-based conservation has emerged as the 'panacea' to the environmental crises we face today. A prominent example of this trend is REDD+, which turns terrestrial carbon in the global South into fictitious commodities that can be sold for profit. In this paper, we conceptualise REDD+ as a form of 'inclusive' neoliberal conservation, highlighting how neoliberalism has embraced notions of good governance, local ownership, social safeguards and active citizenship when promoting global conservation markets. While demonstrating the genuine efforts by project proponents to practice 'inclusion', we highlight their limits due to larger structural inequalities and demonstrate how the commodification of carbon inevitably causes new forms of inclusion and exclusion to local forest users. Based on ethnographic fieldwork in two forest-dependent villages in the Lindi Region of Tanzania, where two different REDD+ projects were underway, we show how material and discursive powers shaped 'inclusive' strategies to market forest-carbon. We then locate these strategies, concerned with the commodification of forest-carbon, within a historical field of power struggles and local politics over forest resources, strongly evidenced in contestations around establishing community-based forest management. We argue that a sharp disjuncture operated between the 'inclusive' strategies to market forest-carbon and the historical dimensions and power relations within the area; resulting in new forms of inclusions and exclusions, both in and outside rural villages.